Stratified round Robin a low complexity packet scheduler with bandwidth fairness and bounded delay. - Ramabhadran, Sriram (Computer communication review.)
Fair queuing is a well-studied problem in modern computer networks. However, there remains a gap between scheduling algorithms that have provably good performance, and those that are feasible and practical to implement in high speed routers. In this paper, we propose a novel packet scheduler called Stratified Round Robin, which has low complexity, and is amenable to a simple hardware implementation. Stratified Robin Robin exhibits good fairness and delay properties that are demonstrated through both analytical results and simulations. In particular, it provides a single packet delay bound that is independent of the number of flows. This property is unique to Stratified Round Robin among all other schedulers of comparable complexity.